Manga and militarism: rehabilitating military violence in Japan. - Warrack, Max (Pacific Review, 2025)
There is an impasse in Japan's security debate. Realists emphasise defence build-up programmes and policy reforms that are cumulatively developing Japan's autonomous security capabilities to argue Japan is remilitarising; and normative constructivists emphasise a 'culture of antimilitarism' to argue it is not really remilitarising. This article explores a route through this impasse by flipping the premise on which it rests: that Japan's culture resists remilitarisation. It investigates manga (Japanese comics) that positively portray the Japan Self-Defense Force (JSDF) enacting violence. Through a content analysis of these manga, it identifies three patterns of violence: constrained, frantic, and dominant, that frame JSDF violence as a legitimate tool of statecraft. They represent an interpretive challenge to the antimilitarist societal consensus; one this article outlines using Jeffrey Alexander's New Durkheimian conceptualisation of civil society. The article traces the industry-origins of these manga and illustrates (pun intended) how they disrupt the 'culture of antimilitarism'. The article outlines a process of 'cultural remilitarisation' connected to Japan's most prominent medium, presenting a cultural explanation for Japan's post-Cold War security trajectory; and introducing nuance to a key premise of the Japan security debate: Japan's culture can support and encourage, as well as resist, remilitarisation.